The effect of corvitin on the indicators of the nitric oxide system in the kidneys under the conditions of the development of experimental pneumonia and adrenaline damage to the myocardium - M. Regeda; N. Shklyarskyi (Journal of Education, Health and Sport)
Currently, the effect of corvitin on the indicators of the nitric oxide system in the kidneys in experimental pneumonia (EP) and adrenaline damage to the myocardium (APM) is not studied. The aim of our study was to find out the effect of the corvitin drug on the disturbed markers of the nitric oxide system in the kidneys in EP and APM.